Analysis of Rainwater Harvesting as An Alternative to Non-Domestic Water Supply at PLN Institute of Technology at PLN Institute of Technology - Lestari, Endah; Arizki, Rahmad (Institute Of Advanced Knowledge and Science, 2025)
Clean water is one of the targets in the Sustainable Development Goals (SDG's), specifically ensuring the availability and sustainability of water management. Continued use of groundwater results in land subsidence. The high level of rainfall in Jakarta requires rainwater to be utilized to reduce surface water runoff, especially by rainwater harvesting. PLN Institute of Technology has a total of more than 3.000 employees and students. Based on the use of non-domestic water needs in universities per day for universities of 10 liters/student/day. The volume of rainwater generated by the roof area of PLN Institute of Technology with an area of 1.024 m2 and the mainstay rainfall from 2012 to 2022 was obtained a total of 2.159,18 m3 per year. The storage tanks are made the size of each storage tank that can accommodate a volume of water of 300 m3 with a length of 15 meters, a width of 10 meters and a depth of 2 meters. By using the rainwater harvesting system at PLN Institute of Technology based on the calculation of the potential for meeting water needs, there is an excess of harvested rainwater of 1,202.78 m3 when the number of users is 10% and as much as 248.78 m3 when the number of users is 20% that can be accommodated for use.